EFFECT OF ANTHROPOGENIC CO2 ON THE pH AND THE SATURATION STATES OF CALCITE AND ARAGONITE OF SEAWATER - 陈镇东 王树伦 (Chinese journal of oceanology and limnology, 1997)
Growth of phytoplankton, zooplankton and probably most other marine organisms as well, is likely to be affected by the pH of seawater. Growth of calcareous shells and skeletons is less likely to be affected by the saturation states of calcite and aragonite but the dissolution is.The increase of CO₂ in the oceans due to burning of fossil fuel and clearing of forests is decreasing the pH of seawater and the degrees of saturation for calcite and aragonite wordwide. This paper presents the results of the first attempt to estimate the vertical distribution of anthropogenic CO₂, and the decreases in pH and the degrees of saturation of calcite and aragonite in seawater near Taiwan. Most effects are very small except for the possible dissolution of aragonite on the upper continental slope starting around 2050 AD.